Case 3764: Cuvierina columnella, C. atlantica, C. spoeli (Mollusca, Gastropoda, Euthecosomata). - Rampal, Jeannine (Bulletin of Zoological Nomenclature)
Acknowledgement of receipt published in BZN 75: 3. Case closure notice published in BZN 77: 156.